Use of Oil Palm Shell as Replacement of Coarse Aggregate for Investigating Properties of Concrete - Khan, M. M. H*; Guong, Wei L; Deepak, T. J*; Nair, S.* (Research India Publications, 2016)
In Malaysia, oil palm shell (OPS) is an agricultural solid waste originating from the palm oil industry. In this short-term investigation, old OPS is used for production of lightweight concrete. The density, workability, cube compressive strength and water absorption are measured. Laboratory curing condition is also employed. The test results show that with the increasing amounts of normal aggregates replaced by OPS, the overall density and strength of the lightweight concrete has reduced gradually. The compressive strength of lightweight concrete by combination with 10 % OPS and 90 % coarse aggregate is found to be similar with the normal lightweight concrete from 100% coarse aggregate. And with the increasing amounts of aggregates replaced by OPS, water absorption of the lightweight concrete has increased gradually. It is concluded that OPS concrete has sufficient strength to be accepted as structural lightweight concrete and that the trend of behaviour of OPS concrete and control concrete is very similar.